Analisis SWOT Pada Dinas Kebudayaan dan Pariwisata Kabupaten Blitar dalam Menentukan Strategi Pengembangan Destinasi Pariwisata - Pratama, Wildan Cahya; Isbandono, Prasetyo (Jurnal Inovasi Administrasi Negara Terapan (Inovant), 2023)
The development of the tourism sector is one of the efforts that can be made by the regional government to obtain regional original income. This study aims to determine, describe and analyze the appropriate strategy of the Government of Blitar Regency through the Department of Culture and Tourism in developing regional tourism in Blitar Regency. This type of qualitative research is descriptive and theoretical approach used for this study with SWOT analysis by examining each SWOT indicator with HR, Funds, Information, Infrastructure. There are two types of data, namely Primary (main) and Secondary (assistant) data. Data collection techniques by observation, interviews and documentation and data analysis techniques by reducing data, presenting data, drawing conclusions and verifying. The results of this study are SWOT analysis namely Strengths, Weaknesses, Opportunities, Threats which are then seen from the four strategic indicator factors, namely Human Resources, Funds, Information, and Infrastructure. it can be concluded that placing the tourism sector in the main focus on regional development funding, maximizing funds for the formation of tourism human resources and for the development and development of tourism destinations, as well as facilitating tourism destinations with public facilities, working together with all official parties to carry out development and development of tourism both in terms of accessibility and tourism infrastructure, Providing naming and directions in several tourist attractions and TIC (Tourist Information Center) or Tourism Information Center   Keywords: SWOT analysis, strategy, tourism development